Umbilical Stump Colonization and Antibiotic Susceptibility Patterns of Bacteria from Umbilical Stumps of Neonates Admitted at Holy Innocents Children’s Hospital, Mbarara, South Western Uganda - Mukundane, Bruno; Bazira, Joel; Musinguzi, Benson; Byarugaba, Frederick (Research square, 2023)
Introduction: Every year a million deaths of neonates occur worldwide due to bacteria that has ascended through the umbilical stump leading to serious infection. An umbilical stump that has just separated is known to be the best route for bacterial entrance leading to development of serious infections. It also acts as a reservoir for bacteria which potentially may gain access to the blood flow within first 2–3 days of life when the umbilical vein is still patent. During neonatal period, the umbilical stump takes 1-2weeks to fall off under normal circumstances (WHO). Therefore, understanding umbilical stump colonization is relevant within 14 days before the stump falls off. The most common isolated and recovered organisms that are known for colonization of the umbilical stump are Staphylococcus aureus, Escherichia coli and group B Streptococcus. No matter the type of colonizing bacteria, this kind of colonization normally leads to serious life-threatening infection. Objective: The objective of this study was to determine the umbilical stump colonization and antibiotic susceptibility patterns of bacteria isolated from umbilical stumps of neonates admitted at Holy Innocents Children’s Hospital. Methods: This study used a cross-sectional study and 200 participants were enrolled from neonatal ward in the period of May-June 2022. Samples were aseptically taken off from neonates using a sterile cotton swab which were then cultured and the colonizing organisms isolated after which antimicrobial susceptibility testing was done using Kirby Bauer disk diffusion method. Results: After culture of 200 samples, only 35 (17.5%) showed growth. Of the isolated organisms Staphylococcus aureus had the highest number of 15 (42.9%), this was followed by E. coli with 8 (22.9%), then K.pneumoniae at 4 (11.4%), Proteus spp at 4 (11.4%, then Streptococcus spp at 2 (5.7) and finally Pseudomonas spp at 2 (5.7%). All Staphylococcus species were sensitive to Vancomycin whereas all E. coli species were resistant to Imipenem, Tetracycline, Erythromycin and Ampicillin. All Klebsiella and Streptococcus species were 100% sensitive to Ciprofloxacin, Chloramphenicol and Gentamicin. Chloramphenicol had the highest sensitivity of 85.7% followed by Gentamicin at 62.9% and Trimethoprimsulfamethoxazole had the highest resistance of 62.9% which was followed by Tetracycline with the resistance of 54.3%. All Streptococcus species were sensitive to Cefoxitin, Chloramphenicol, Erythromycin and Clindamycin whereas all Pseudomonas species were sensitive to Ceftazidime, Piperacillin and Piperacillin-tazobactam. Conclusion: The prevalence of umbilical stump colonisation at HICH was high at 17.5% and the main causative agents are Staphylococcus aureus and Escherichia.coli. These organisms are resistant to commonly used antibiotics like Ciprofloxacin, Ceftriaxone and Amoxicillin-Clavulanic acid.
Keywords: Umbilical; Stump; Colonization; Antibiotic; Neonates